Regional travel-time residual studies and station correction from 1-D velocity models for some stations around Peninsular Malaysia and Singapore - Osagie, Abel U.; Mohd. Nawawi, Mohd. Nawawi; Khalil, Amin Esmail; Abdullah, Khiruddin (Elsevier, 2017)
We have investigated the average P-wave travel-time residuals for some stations around Southern Thailand, Peninsular Malaysia and Singapore at regional distances. Six years (January, 2010–December, 2015) record of events from central and northern Sumatra was obtained from the digital seismic archives of Integrated Research Institute for Seismology (IRIS). The criteria used for the data selection are designed to be above the magnitude of mb 4.5, depth less than 200 km and an epicentral distance shorter than 1000 km. Within this window a total number of 152 earthquakes were obtained. Furthermore, data were filtered based on the clarity of the seismic phases that are manually picked. A total of 1088 P-wave arrivals and 962 S-wave arrivals were hand-picked from 10 seismic stations around the Peninsula. Three stations IPM, KUM, and KOM from Peninsular Malaysia, four stations BTDF, NTU, BESC and KAPK from Singapore and three stations SURA, SRIT and SKLT located in the southern part of Thailand are used. Station NTU was chosen as the Ref. station because it recorded the large number of events. Travel-times were calculated using three 1-D models (Preliminary Ref. Earth Model PREM (Dziewonski and Anderson, 1981, IASP91, and Lienert et al., 1986) and an adopted two-point ray tracing algorithm. For the three models, we corroborate our calculated travel-times with the results from the use of TAUP travel-time calculation software. Relative to station NTU, our results show that the average P wave travel-time residual for PREM model ranges from −0.16 to 0.45 s for BESC and IPM respectively. For IASP91 model, the average residual ranges from −0.25 to 0.24 s for SRIT and SKLT respectively, and ranges from −0.22 to 0.30 s for KAPK and IPM respectively for Lienert et al. (1986) model. Generally, most stations have slightly positive residuals relative to station NTU. These corrections reflect the difference between actual and estimated model velocities along ray paths to stations and can compensate for heterogeneous velocity structure near individual stations. The computed average travel-time residuals can reduce errors attributable to station correction in the inversion of hypocentral parameters around the Peninsula. Due to the heterogeneity occasioned by the numerous fault systems, a better 1-D velocity model for the Peninsula is desired for more reliable hypocentral inversion and other seismic investigations.